Optimizing Monetary Policy Transmission Through The Emerging Market Interest Rate Channel - Wahyu Indah Sari; Ade Novalina; Annisa Sanny (Universitas Kristen Indonesia Toraja, 2022)
Research using the ARDL Panel Model includes Inflation, Gross Domestic Product, Total Money Supply, Exchange Rates, Consumption, Investment, and Interest Rate in Asia's Three Emerging Markets namely India, China, and Indonesia which aims to boost the economy. This study uses secondary data with a quantitative research type using ARDL Panel Regression, the software used is Eviews 10 with cross-section data for 3 Emerging Market Countries, namely India, China, and Indonesia time series data for 2001-2020. The research results show that Exchange Rates, Investments, and Interest Rates can also be leading indicators to support price stability in Indonesia, China, and India, but their positions are unstable in the long run and short run. The main leading indicator in optimizing the variables in controlling price stability in the Three Emerging Markets Asia is Consumption seen from the stability of the short run and long run, where the long-term and short-term interest rate variables are significant in controlling price stability.